Phosphorylation of alphaB-crystallin alters chaperone function through loss of dimeric substructure. - Aquilina, J; Benesch, J; Robinson, C; al., E (American Society for Biochemistry and Molecular Biology, 2004)
Phosphorylation is the most common posttranslational modification of the α-crystallins in the human lens. These phosphorylated forms are not only important because of their abundance in aging lenses and the implications for cataract but also because they have been identified in patients with degenerative brain disease. By using mimics corresponding to the reported in vivo phosphorylation sites in the human lens, we have examined the effects of phosphorylation upon the chaperone-like properties and structure of αB-crystallin. Here we show that phosphorylation of αB-crystallin at Ser-45 results in uncontrolled aggregation. By using an innovative tandem mass spectrometry approach, we demonstrate how this alteration in behavior stems from disruption of dimeric substructure within the polydisperse αB-crystallin assembly. This structural perturbation appears to disturb the housekeeping role of αB-crystallin and consequently has important implications for the disease states caused by protein aggregation in the lens and deposition in non-lenticular tissue.